Compensating Hand Function in Chronic Stroke Patients Through the Robotic Sixth Finger - Salvietti, Gionata; Hussain, Irfan; Cioncoloni, David; Taddei, Sabrina; Rossi, Simone; Prattichizzo, Domenico (IEEE transactions on neural systems and rehabilitation engineering, 2017)
A novel solution to compensate hand grasping abilities is proposed for chronic stroke patients. The goal is to provide the patients with a wearable robotic extra-finger that can be worn on the paretic forearm by means of an elastic band. The proposed prototype, the Robotic Sixth Finger, is a modular articulated device that can adapt its structure to the grasped object shape. The extra-finger and the paretic hand act like the two parts of a gripper cooperatively holding an object. We evaluated the feasibility of the approach with four chronic stroke patients performing a qualitative test, the Frenchay Arm Test. In this proof of concept study, the use of the Robotic Sixth Finger has increased the total score of the patients by two points in a five points scale. The subjects were able to perform the two grasping tasks included in the test that were not possible without the robotic extra-finger. Adding a robotic opposing finger is a very promising approach that can significantly improve the functional compensation of the chronic stroke patient during everyday life activities.